2017
DOI: 10.1111/ele.12748
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area

Abstract: Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether droughtinduced mortality rates differ among global biomes and whether functional traits influence the risk of drought-induced mortality. To address these uncertainties, we performed a global metaanalysis of 58 studies of drought-induced forest mortality. Mortality rates were modelled as a function of drought, temperature, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
335
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(394 citation statements)
references
References 142 publications
(306 reference statements)
18
335
4
4
Order By: Relevance
“…For example, recent studies evidenced how some functional traits as wood density (Greenwood et al 2017), stand conditions as inter-and intra-specific competition, the level of crown transparency or the size and age of plants, co-act with drought in leading to decline. In fact, in accordance with Martínez-Vilalta et al (2011), intra-and interspecific competition exacerbates the negative effects of drought predisposing plants to decline.…”
Section: Causes and Mechanisms Leading To Oak Declinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent studies evidenced how some functional traits as wood density (Greenwood et al 2017), stand conditions as inter-and intra-specific competition, the level of crown transparency or the size and age of plants, co-act with drought in leading to decline. In fact, in accordance with Martínez-Vilalta et al (2011), intra-and interspecific competition exacerbates the negative effects of drought predisposing plants to decline.…”
Section: Causes and Mechanisms Leading To Oak Declinementioning
confidence: 99%
“…For instance, Greenwood et al (2017) concluded that tree mortality increased with drought severity, but functional traits as wood density explained less than 10% of the variation in drought responses, although tree species with denser wood showed lower mortality responses. Remarkably, only 17% of their 58 study cases considered oak species.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Gridded drought indices have been widely used in a variety of systems to identify drought impacts, including tree morbidity and mortality at various spatial scales [43,44], crop yield reductions and crop failures [45], forest fires [46,47], and decreased vegetation activity [48,49]. The developed …”
Section: Data Use and Applicationmentioning
confidence: 99%
“…Since dry spells reduce forest productivity and tree growth and often weaken trees by deteriorating their vigor, drought effects on forests may last for several years (Peltier et al, 2016). Recent studies suggest that forest resilience to drought, i.e., the capacity to resist and recover after a drought, mainly depends on drought intensity, but such resilience may also depend on climate types (Zhang et al, 2017), tree species or specific functional traits (Greenwood et al, 2017). Furthermore, tree species and individuals can vary in their strategies to cope with drought (Gazol et al, 2017a,b) modifying forest growth responses to drought, which may be reflected in tree-ring width variability.…”
Section: Introductionmentioning
confidence: 99%